PUBLIC AFFECTIVE RESPONSES TOWARD THE FREE NUTRITIOUS MEALS POLICY (MAKAN BERGIZI GRATIS/MBG): EVIDENCE FROM CENTRAL KALIMANTAN - Salsha Kurnia Dewi; Laila Kholid Alfirdaus (SOSIOEDUKASI, 2026)
This study examines public affective responses toward the implementation of the Free Nutritious Meal Program (MBG) in Central Kalimantan following Indonesia’s 2024 presidential election. While MBG was promoted as a flagship welfare policy aimed at improving child nutrition and reducing household burdens, its post-election implementation generated mixed public reactions. Drawing on Affective Intelligence Theory, this research analyzes how emotions such as enthusiasm, anxiety, and anger shape citizens’ evaluations of welfare policy beyond rational assessments of performance. Employing a mixed-methods design, the study integrates survey data from 50 respondents with in-depth interviews involving 10 informants. Quantitative data capture patterns of affective response and perceived policy quality, while qualitative data provide contextual insight into lived experiences with MBG implementation. The findings reveal that public support for MBG remains present but conditional. Enthusiasm toward the program’s objectives coexists with significant anxiety related to food safety, nutritional adequacy, and program sustainability, as well as situational anger directed at implementation failures rather than at the policy idea itself. These results demonstrate that public responses to welfare policy in a politically supportive region are emotionally complex and evaluative. Anxiety functions as a trigger for critical engagement and information-seeking behavior, while anger reflects demands for accountability rather than outright rejection. The study contributes to the literature on political emotions and public policy by highlighting the importance of affective dynamics in post-electoral governance and by extending the application of Affective Intelligence Theory to the analysis of welfare policy implementation in Indonesia.